2018
DOI: 10.1097/md.0000000000010521
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent PR3-ANCA-positive hypertrophic pachymeningitis

Abstract: Rationale:Hypertrophic pachymeningitis (HP) is an uncommon, life-threatening disease that is seen in elderly patients with antineutrophil cytoplasmic antibody (ANCA) positivity. Proteinase-3 (PR3)-ANCA-positive HP has not been reported in adolescents. Here, we report the first case of adolescent PR3-ANCA-positive HP successfully treated with immunosuppressive therapy.Patient concerns:A 14-year-old female presented with fullness and pain in her right ear unresponsive to antibiotics. Laboratory tests showed an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
1
6
0
2
Order By: Relevance
“…We showed that changes in plasma cells were strongly correlated with the reactivation of CNS disease. This hypothesis is supported by our recent finding of a significant correlation between circulating B cells and the CNS component of BVAS [21,38]. CNS lesion may be a good indicator of the need for B cell depletion therapy in AAV.…”
Section: Discussionsupporting
confidence: 63%
“…We showed that changes in plasma cells were strongly correlated with the reactivation of CNS disease. This hypothesis is supported by our recent finding of a significant correlation between circulating B cells and the CNS component of BVAS [21,38]. CNS lesion may be a good indicator of the need for B cell depletion therapy in AAV.…”
Section: Discussionsupporting
confidence: 63%
“…We performed a review of the literature (Medline 1990–present) using the search terms (hypertrophic pachymeningitis) AND (paediatric OR pediatric OR children OR childhood). Twelve cases referring to children (<18 years old) were identified and the full manuscripts were available for review [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the twelve pediatric cases of hypertrophic pachymeningitis reported in the literature, three cases developed in association with tuberculosis [ 10 , 11 , 17 ], one was PR3-ANCA-associated [ 13 ], two developed in association with IgG4-RD [ 16 , 18 ] and six were regarded as idiopathic [ 7 , 8 , 9 , 12 , 14 , 15 ]. The clinical features, MRI findings, biopsy results, treatment and outcomes are summarized in Table 2 .…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor: I read with great interest the article by Delaval et al reporting on their study of the largest case series of temporal arteritis (TA) in antineutrophil cytoplasmic antibody (ANCA)-associated vasculitides (AAVs), including clinical, serologic, and histologic manifestations (1). Recent progress in the understanding of AAV has revealed that it can present rare, atypical manifestations, such as isolated dacryosialadenitis, isolated retroperitoneal fibrosis, and isolated hypertrophic pachymeningitis (2)(3)(4). Therefore, in such cases, it is important to recognize AAV as one of the differential diagnoses and to conduct histologic examination and ANCA testing for appropriate disease management.…”
Section: Recognition Of Rare Atypical Manifestations Is Important For Diagnosis and Management Of Antineutrophil Cyto Plasmic Antibody-asmentioning
confidence: 99%